2007
DOI: 10.1242/jcs.03393
|View full text |Cite
|
Sign up to set email alerts
|

Survivin mediates the anti-apoptotic effect of δ-opioid receptor stimulation in cardiomyocytes

Abstract: Survivin is known to be essential for cell division and to inhibit apoptosis during embryonic development and in adult cancerous tissues. However, the cardiovascular role of survivin is unknown. We observed that in cardiomyocytes cultured under conditions of serum and glucose deprivation (DEPV), the levels of survivin, Bcl-2 and extracellular signal-regulated kinase (ERK) were positively correlated with the anti-apoptotic action of a δ-opioid receptor agonist, [D-Ala2, D-Leu5]-enkephalin acetate (DADLE). By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Our data are consistent with results in cells exposed to ciglitazone in A172 human glioma cells [49]. It has been reported that ERK or Akt can be an upstream regulator of XIAP and survivin [50][51][52]. However, whether ERK and Akt are involved in regulating XIAP and survivin in glioma cells remains to be further elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Our data are consistent with results in cells exposed to ciglitazone in A172 human glioma cells [49]. It has been reported that ERK or Akt can be an upstream regulator of XIAP and survivin [50][51][52]. However, whether ERK and Akt are involved in regulating XIAP and survivin in glioma cells remains to be further elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Yao et al (33) reported that activation of the δ-opioid receptor reduces the apoptosis of myocardial cells through inhibition of the ERK and IP3 pathways. Furthermore, Huang et al (34) reported that activation of the δ-opioid receptor inhibits apoptosis by promoting CGRP expression in myocardial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pellet was resuspended into 30 µL of cold lysis buffer (at pH 7.5, in mmol/ L, 20 Tris, 100 NaCl, 1% Triton X-100) supplemented with 1% protease inhibitor cocktail. The supernatant was further centrifuged at 100,000 g for 60 min at 4°C, and the resultant supernatant was collected as the cytosolic fraction [16,17].…”
Section: Western Blottingmentioning
confidence: 99%